2019
DOI: 10.1016/j.enconman.2019.112069
|View full text |Cite
|
Sign up to set email alerts
|

An innovative energy management framework for cooperative operation management of electricity and natural gas demands

Abstract: Introduction of the power to gas and combined heat and power technologies, has led to remarkable interdependency between electrical and gas systems. By taking advantage of this interdependency, cleaner and more efficient energy management systems could be implemented. This paper attempts to establish an innovative energy management framework which takes advantage of this interdependency and devices like power to gas and combined heat and power to simultaneously smoothen electricity and natural gas demand profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A twostage model for combined gas and power networks is proposed in [18] by studying the uncertain parameters. The authors have proposed an innovative energy management model in [19] for smoothening gas and power load patterns by taking advantage of interconnection among power and gas networks and technologies such as the power to gas and CHP units.…”
Section: 2literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A twostage model for combined gas and power networks is proposed in [18] by studying the uncertain parameters. The authors have proposed an innovative energy management model in [19] for smoothening gas and power load patterns by taking advantage of interconnection among power and gas networks and technologies such as the power to gas and CHP units.…”
Section: 2literature Reviewmentioning
confidence: 99%
“…Equations ( 17) and (18) show the limitation of the conversion of power to hydrogen and hydrogen to gas. Equation (19) shows the amount of energy available in the hydrogen storage system.…”
Section: 1constraintsmentioning
confidence: 99%
“…In the cooperative methods, the objective is to find the Pareto optimal solution of the problem, but finding the equilibrium point is the objective in the non-cooperative models. The authors in [12] proposed a cooperative model including power to gas (P2G) devices for integrated power and gas networks and considered the demand smoothness and cost reduction in the network. Nevertheless, the effect of cooling system, demand response program, and fair allocation of costs are not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that strategic coordination would aid in addressing several practical challenges in natural gas systems, including natural gas leakage [16], rapid changes and significant uncertainties in gas demand [15], and natural gas-supply bottlenecks [6], etc. Additionally, integrated gas-electricity planning and operation is helpful in tackling the challenges frequently witnessed in electric power systems, such as (1) the substantial gap between peaks and valleys of demand profiles [17], (2) the inherently stochastic characteristics of renewable production [18], (3) the poor performance of electricity demand prediction [19], etc. Furthermore, the unwillingness of both natural gas and electricity system operators to share proprietary information is taken into account in numerous studies.…”
Section: Literature Reviewmentioning
confidence: 99%